Writing and contextualising local history. A historical narrative of the Wellington Horticultural Society (Coloured) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The purpose of this study was to enhance local history as a focus area in a Higher Education (HE) teaching context. This article documented a case study of the practice of flower growing as a recreational-competitive activity. A historical narrative was thus constructed around the Wellington Horticulture Society (Coloured), henceforth referred to as the (WHS). The founding of the WHS coincided with the emergence of cultural organisations in Wellington. Furthermore, it was part of a social development, known as garden culture. By using documentary evidence, previous research material and an oral historical account, a narrative of the WHS was created, emphasising aspects, such as competition, family history and garden culture. This research identified social and political dilemmas associated with the WHS.
Keywords: Competition; Family; Historical thinking; Gardern Culture; Local history